2013
DOI: 10.4314/ejesm.v6i6.6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Farmers’ Response to Climate Variability in Nigeria: A Multinomial Logit Approach

Abstract: In Nigeria, farming still depends largely on nature and therefore, vulnerable to climate variability. Climate variability affects production in a number of ways such as uncertainties with the onset of the farming season, flooding and drought in some areas .Farmers have responded by using adaptation strategies. The determinants of farmers' use of these strategies have not been adequately ascertained. In this study, farmers 'response to climate variability was examined. Primary and secondary data were used. A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
2
4
2
1
Order By: Relevance
“…Accordingly, farmers who were aware of the Hybrids and improved OPVs and thought they gave benefits such as immediate benefits, increased yield and improving households" food security were likely to use them relative to the traditional seeds. These results concur with research that found that if farmers believe that DTSVs were responsible for high yield and enhanced food security, they are most likely to adopt them to improve their livelihood (Diale, 2011;Ikheloa et al, 2013;Senyolo et al, 2018).…”
Section: Knowledge Possession and Benefits Related To Dtsvssupporting
confidence: 86%
See 3 more Smart Citations
“…Accordingly, farmers who were aware of the Hybrids and improved OPVs and thought they gave benefits such as immediate benefits, increased yield and improving households" food security were likely to use them relative to the traditional seeds. These results concur with research that found that if farmers believe that DTSVs were responsible for high yield and enhanced food security, they are most likely to adopt them to improve their livelihood (Diale, 2011;Ikheloa et al, 2013;Senyolo et al, 2018).…”
Section: Knowledge Possession and Benefits Related To Dtsvssupporting
confidence: 86%
“…While access to government support (i.e. formal extension services) usually influence adoption of technologies positively (Diale, 2011;Ikheloa et al, 2013), this was not the case in our study. Our data shows negative but insignificant relationship between government support and the use of DTSVs.…”
Section: Socioeconomic Characteristics Of Surveyed Farmers In Limpopo Province South Africacontrasting
confidence: 65%
See 2 more Smart Citations
“…Cette forte variabilité aussi bien temporelle, spatiale que quantitative des précipitations rend les systèmes de production agricole plus vulnérables et constitue une contrainte majeure aux objectifs d'autosuffisance alimentaire que se sont fixés les pays de l'Afrique de l'Ouest (Agbossou, 2010). La variabilité climatique affecte la production de plusieurs façons par les incertitudes avec le début de la saison agricole, les inondations et la sécheresse dans certaines zones (Ikheloa et al, 2013). L'évolution des conditions climatiques a de graves répercussions négatives sur la production agricoles, la sécurité alimentaire et les ressources naturelles (Agbongiarhuoyi et al, 2013).…”
Section: Introductionunclassified